Research brief: Value chain and market potential of Chaya to strengthen climate resilience, nutrition security and incomes in Guatemala - Amaya, N.; Meldrum, G.; Padulosi, S.; Cifuentes, R. (Bioversity International, 2018)
Chaya (Cnidoscolus aconitifolius) is a perennial vegetable native to Guatemala, which has potential to make significant nutritional and health contributions in vulnerable communities due to its high nutritional value and capacity to produce leaves yield year-round. Chaya can be considered as a ‘superfood’ and as a viable option for an economic food supply for the Guatemalan population. Yet, paradoxically, its production, consumption and marketing have been poorly studied and promoted insofar. In 2017, a value chain assessment was carried out by Bioversity International and the Universidad del Valle de Guatemala (UVG) to contribute to fill this gap in knowledge, and identify opportunities and constraints for developing the market of chaya in Guatemala. This study deployed a Rapid Market Appraisal methodology to collect qualitative data through semi-structured interviews of different stakeholders engaged in the chaya value chain, including producers, vendors, consumers, indirect actors and other informed participants. This brief presents some key results of this research.